Revisiting diagnostic criteria for myelodysplastic/myeloproliferative neoplasms with ring sideroblasts and thrombocytosis: Borderline cases without anemia exist. (27th February 2019) - Li, Peng; Shahmarvand, Nahid; Lynch, David; Gotlib, Jason R.; Merker, Jason D.; Zehnder, James L.; George, Tracy I.; Ohgami, Robert S.
Abstract: Introduction: Myelodysplastic/myeloproliferative neoplasm with ring sideroblasts and thrombocytosis (MDS/MPN‐RS‐T) is a rare disease in the 2016 revised World Health Organization (WHO) classification. Diagnostic criteria include the following: persistent thrombocytosis (>450 × 10 9 /L) with clustering of atypical megakaryocytes, refractory anemia, dyserythropoiesis with ring sideroblasts, and the presence of the spliceosome factor 3b subunit ( SF3B1 ) mutation. It is unclear if anemia should be a required criterion for this diagnosis as cases which show all other features of MDS/MPN‐RS‐T but without anemia exist. Methods: We searched for borderline cases of MDS/MPN‐RS‐T in which refractory anemia was absent at diagnosis in two major academic institutes. Results: Three cases without anemia were identified. These cases all showed other classic morphologic and clinical features of MDS/MPN‐RS‐T, including thrombocytosis, atypical megakaryocytes with clustering, and characteristic SF3B1 and JAK2 V617F mutations. Conclusion: Given these findings, the requirement of refractory anemia as a diagnostic criterion for MDS/MPN‐RS‐T should be re‐evaluated. Removal of refractory anemia as a diagnostic criterion would incorporate current borderline cases and extend the spectrum of this disorder.